RESERVOIR PROPERTIES OF CARBON ROCKS OF THE HNIDYNTSIVSKE OIL AND GAS CONDENSATE DEPOSIT OF THE GLYNSKO-SOLOKHIV GAS CONDENSATE FIELD - VYZHVA, Serhii; ONYSHCHUK, Viktor; ONYSHCHUK, Dmytro; ONYSHCHUK, Ivan; SHABATURA, Oleksandr (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The paper concerns the results of reservoir properties determination of carbon rocks of the Hnidyntsivske oil and gas condensate deposit of the Glynsko-Solokhiv gas condensate field with the purpose of looking into comprehensive analysis of their physical features.Methods. A brief petrographic description of limestones was performed. The bulk density of dry rock samples (matrix density of the rock) is determined by weighing and measuring their geometric dimensions. Hydrostatic weighing method was applied to the rock samples saturated with kerosene. The open porosity coefficient was determined by the gas volumetric method and the method of hydrostatic weighing according to the standard methodology. Capillarometric studies were performed by centrifugation of rock samples.Results. Such reservoir features of rock samples as open porosity coefficient and effective porosity coefficient, residual oil saturation factor and permeability coefficient were researched. The limits of variation and mean values of the reservoir properties of the studied rocks are given. The capillarometric studies by the method of centrifugation helped to understand the structure of the void space of rocks.Conclusions. The correlation analysis was applied to establish a number of correlations between the reservoir parameters of the studied rocks – density, open porosity coefficient, effective porosity coefficient and residual water saturation factor, as well as between the porosity coefficients measured in atmospheric and reservoir conditions. These correlations can be used for the interpretation of well logging data and modeling of reservoir parameters of consolidated reservoir rocks.
Keywords: limestones; density; porosity coefficient; permeability coefficient; residual oil saturation factor; correlation relationships; reservoir properties